Nicola gen. nov. with redescription of Nicola tetela (Borojevic & Peixinho, 1976) (Porifera: Calcarea: Calcinea: Clathrinida) - Cóndor-Luján, B.; Klautau, M. (Zootaxa, 2016)
Guancha tetela was originally described as a species having a peduncle and a skeleton exclusively composed of sagittal triactines. Therefore, according to the most recent phylogeny of Clathrinida, it should be placed in the genus Clathrina. This species was collected on the Northeastern Brazilian coast in 1968 and it was not collected again until 2011 in Curaçao. In this study, we reanalyzed the type material and the new specimens from Curaçao under a morphological-molecular approach. Morphological analysis revealed the presence of tetractines in the skeleton of all the studied specimens, including a slide of the holotype. In the molecular phylogeny G. tetela grouped with genera containing tetractines, but as an independent new lineage, different from all the other genera of Clathrinida. Based on these results, we propose the erection of a new genus, Nicola gen. nov., to include species whose body is composed of tubes without anastomosis nor branches but that run in parallel and coalesce at the apical and basal regions. Moreover, the skeleton is exclusively composed of sagittal triactines and tetractines.